Impacts of Shifts in Phytoplankton Community on Clouds and Climate via the Sulfur Cycle. Issue 6 (27th June 2018) - Wang, Shanlin; Maltrud, Mathew E.; Burrows, Susannah M.; Elliott, Scott M.; Cameron‐Smith, Philip
Abstract: Dimethyl sulfide (DMS), primarily produced by marine organisms, contributes significantly to sulfate aerosol loading over the ocean after being oxidized in the atmosphere. In addition to exerting a direct radiative effect, the resulting aerosol particles act as cloud condensation nuclei, modulating cloud properties and extent, with impacts on atmospheric radiative transfer and climate. Thus, changes in pelagic ecosystems, such as phytoplankton physiology and community structure, may influence organosulfur production, and subsequently affect climate via the sulfur cycle. A fully coupled Earth system model, including explicit marine ecosystems and the sulfur cycle, is used here to investigate the impacts of changes associated with individual phytoplankton groups on DMS emissions and climate. Simulations show that changes in phytoplankton community structure, DMS production efficiency, and interactions of multielement biogeochemical cycles can all lead to significant differences in DMS transfer to the atmosphere. Subsequent changes in sulfate aerosol burden, cloud condensation nuclei number, and radiative effect are examined. We find the global annual mean cloud radiative effect shifts up to 0.21 W/m 2, and the mean surface temperature increases up to 0.1 °C due to DMS production changes associated with individual phytoplankton group in simulations with radiative effects at the 2, 100 levels under an 8.5 scenario. However, changes in DMS emissions, radiative effect, and surface temperature are more intensive on regional scales. Hence, we speculate that major uncertainties associated with future marine sulfur cycling will involve strong region‐to‐region climate shifts. Further understanding of marine ecosystems and the relevant phytoplankton‐aerosol‐climate linkage are needed for improving climate projections. Key Points: Phytoplankton community composition shifts in response to climate change Changes in phytoplankton community composition may have significant impacts on DMS emissions Individual phytoplankton functional groups may affect climate via the sulfur cycle